Pharmaco-Toxicological Determination of Biostimulators - Khatamov Tolmas Tulkinovich; Ne’matov Azizjon Nasimovich (American Journal of Biology and Natural Sciences, 2026)
This article studied the pharmacological effects and safety level of a preparation produced from trout liver on the organism of rabbits. The preparation was added to the feed for a specified period, and the live body weight of the animals was regularly monitored. It was determined that the rabbits in the second experimental group showed a significant increase in body weight, as well as effective stimulation of metabolism and physiological processes.